Enhancing Biomethane Production From Lignite by an Anaerobic Polycyclic Aromatic Hydrocarbon Degrading Fungal Flora Enriched From Produced Water - Gong, Kaiyi; Zhang, Yixuan; Guo, Hongguang; Huang, Zaixing; Urynowicz, Michael; Ali, Muhammad Ishtiaq (Frontiers in Microbiology, 2022)
The coal-degrading ability of microorganisms is essential for the formation of biogenic coalbed methane. The ability to degrade the aromatic compound of coal is more important because it is perceived as the main refractory component for bioconversion. In this paper, a polycyclic aromatic hydrocarbon (PAH) degrading fungal community (PF) was enriched from produced water using phenanthrene as sole carbon source. The goal was to improve both the microbial structure of the methanogenic microflora and its coal-degrading ability. Two strategies were pursued. The first used coal pretreatment with PF (PP), followed by methane production by methanogenic microflora; the second used methane production directly from coal by mixed culture of PF and methanogenic microflora (PM). The results showed that methane productions of PP and PM increased by 29.40 and 39.52%, respectively. After 7 days of cultivation, the fungal community has been altered in PP and PM, especially for Penicillium the proportions of which were 67.37 and 89.81% higher than that in methanogenic microflora, respectively. Furthermore, volatile fatty acid accumulations increased by 64.21 and 58.15%, respectively. The 13C-NMR results showed that PF addition promoted the transformation of aromatic carbons in coal to carboxyl and carbonyl carbons, which contributed greatly to the production of methane together with oxygen-containing functional groups. These results suggest that methane production can be increased by indigenous PAH-degrading fungi by improving the fermentation of aromatics in coal and the generation of volatile fatty acids. This provided a feasible method for enhancing biomethane generation in the coal seam.